Makna Konsep Akuntabilitas dan Transparansi dari Perspektif Al-Kindi - Rahmatika, Armizha; isnalita, isnalita (AL-QARDH, 2018)
Cases of bribery involving auditors and auditees become one form of fraud that is difficult to detect. This is because of both parties are equally enjoying the benefits of the outcome of such unethical and immoral behavior. The increasing number of corruption cases, specifically bribes in the government sector from year to year in Indonesia makes the role of public sector auditors such as BPK RI questioned. In addition, some of the perpetrators of corruption are adherents of Islam, which is interesting to criticize because Islam is a religion that upholds the value of honesty and truth. This research used qualitative research method with postmodernism paradigm because the researcher wanted to study the relevance of classical Islamic philosopher, Al-Kindi